Accidental multiple magnet ingestion by an adult: a case report - Gopal, Suraj; Bhushan, Dubey Indu; Sofi, Junaid Ahmad (International Surgery Journal, 2020)
Accidental multiple magnetic foreign body ingestion although common in children is rare in adults. Multiple magnetic foreign body ingestion possess a definitive risk of causing intestinal perforation, volvulus or fistulas and requires early surgical intervention even in apparently asymptomatic individuals to prevent catastrophic complications. We report a case of an 18 year old male with a history of accidental simultaneous ingestion of two semi-circular shaped magnets along with a nail. The peculiarity of the case being that despite the magnets being simultaneously ingested, one was in the stomach and the other in the jejunum adhered to each other through the transverse colon mesentery causing pressure necrosis of the adjoining wall with the patient being asymptomatic.